2020
DOI: 10.1111/ajt.15978
|View full text |Cite
|
Sign up to set email alerts
|

Living-donor liver transplantation for liver hemorrhaging due to peliosis hepatis in X-linked myotubular myopathy: Two cases and a literature review

Abstract: X‐linked myotubular myopathy (MTM) (OMIM 310400) is a severe neuromuscular disorder caused by mutations in the myotubularin (MTM1) gene. Liver hemorrhaging due to peliosis hepatis (PH) is a fatal complication. We herein report 2 successful cases of living‐donor liver transplantation (LDLT) for MTM patients due to liver hemorrhaging caused by PH and review previous reports. A boy who was 9 years and 4 months old initially underwent left lateral segmentectomy due to massive hepatic and intraperitoneal hemorrhagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies have shown that hepatobiliary disease in patients with XLMTM is independent of the age of the patient or severity of the disease. 1–4 D'Amico et al 2 studied 12 patients with XLMTM for 10 years, and they found that 5 of 12 had elevated transaminases and 7 of 12 had abnormal hepatic echogenicity. Only 1 of 12 had 3 pruritic cholestatic jaundice episodes, and similar to our patient, some of these episodes occurred after exposure to stressors such as infections and were characterized by conjugated hyperbilirubinemia and increase in transaminases and bile acids, while GGT remained normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that hepatobiliary disease in patients with XLMTM is independent of the age of the patient or severity of the disease. 1–4 D'Amico et al 2 studied 12 patients with XLMTM for 10 years, and they found that 5 of 12 had elevated transaminases and 7 of 12 had abnormal hepatic echogenicity. Only 1 of 12 had 3 pruritic cholestatic jaundice episodes, and similar to our patient, some of these episodes occurred after exposure to stressors such as infections and were characterized by conjugated hyperbilirubinemia and increase in transaminases and bile acids, while GGT remained normal.…”
Section: Discussionmentioning
confidence: 99%
“…We present the XLMTM case who developed cholestasis with normal gamma-glutamyl transferase (GGT) at 1 year of age and was then diagnosed with Crohn's disease 4 years later. We propose that his cholestasis is related to XLMTM leading to a progressive familial intrahepatic cholestasis (PFIC)-like state (1)(2)(3)(4) rather than primary sclerosing cholangitis (PSC) or PFIC.…”
Section: Introductionmentioning
confidence: 99%
“…Prior reports emphasize the morbidity/mortality of opposing outcomes: forensic examination of the liver at autopsy to rule out death by suspected caregiver abuse 11 or survival by virtue of emergency, living-related donor liver transplantation. 12 The ASPIRO trial was designed to mitigate this risk by excluding subjects with “clinically significant underlying liver disease” (ClinicalTrials.gov: NCT03199469 ), yet four of the first six patients enrolled were cited in the Audentes letter as having previous histories of hepatobiliary disease.…”
Section: Main Textmentioning
confidence: 99%
“…11,12,15 Recently, the occurrence of PH in humans has also been linked to a genetic predisposition in individuals with X-linked myotubular myopathy. 24 The pathogenesis of the disorder is not yet completely understood, but it is suggested that by direct or indirect cellular endothelial damage the sinusoidal barrier is compromised, and there is sinusoidal dilatation and rupture of the reticulin framework with subsequent perisinusoidal fibrosis. 5,11,13,14,25 Owl monkeys (Aotus spp.)…”
mentioning
confidence: 99%